Kekuasaan dalam Pandangan Negara Konvensional dan Negara Islam - Alsar Andri, Askarmin Harun (Dialektika Publik, 2019)
Power is the opportunity for a person or group of people to make the community aware of their own desires, while simultaneously applying them to the actions of resistance from certain people or groups. Basically, power is intended to protect the people they lead, and that power is to achieve common goals and ideals of the state. With the glory of the power's purpose, power should not be misused, as a tool to enrich oneself, certain groups and parties, and in exercising power that has been achieved has constitutional legitimacy so that it truly has a legal position